Determinasi Organizational Citizenship Behavior (OCB) dan Loyalitas Karyawan: Analisis Pengetahuan, Komitmen Organisasi dan Motivasi Kerja (Studi Literature Review) - Charli, Chintya Ones; Mahzum, Muhammad (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Article literature Review the effect of knowledge, organizational commitment and work motivation on Organizational Citizenship Behavior (OCB)and Employee Loyalty is a scientific article that aims to build a hypothesis of inter-variable influence research that will be used in subsequent research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) knowledge affects Organizational Citizenship Behavior (OCB); 2) organizational commitment affects Organizational Citizenship Behavior (OCB); 2) work motivation affects Organizational Citizenship Behavior (OCB); 4) knowledge affects employee loyalty; 5) organizational commitment affects employee loyalty; 6) work motivation affects employee loyalty.and 7) Organizational Citizenship Behavior (OCB) affect employee loyalty.Â  Selaian of these three exogenous variables that affect the endogenous variables Organizational Citizenship Behavior (OCB)and employee Loyalitystill many other factors among which are variables Persepsidukanorganisasi, decision making, implementation, social and direction.